Structural equations of the relationship between the lifestyle of Women employees with the experience of work immersion with the mediation of organizational commitment - Attaran, Elnaz; Tizdast, Taher; Zarbakhsh Bahri, Mohammad Reza (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The present research was conducted with the aim of structural equations of the relationship between the psychological needs of employees with the experience of flow at work with the mediation of organizational commitment. Methods: The current research method was correlation type and structural equation method was used. All the female employees of the Islamic Azad Universities of Tehran in the academic year of 2019-21 formed the statistical population of the present study, and 339 employees were selected as a sample using the random sampling method. To collect data, a questionnaire tool was used: the questionnaire on the experience of drowning in work Talabighi (2013), psychological needs Deci and Ryan (2000) and the organizational commitment questionnaire Allen and Mayer (1997) were the research tools, which were reliable and valid. Questionnaires in this research were calculated using Cronbach's alpha 0.865, 0.921 and 0.793 respectively for the aforementioned questionnaires. To analyze the data, Pearson's correlation coefficient and structural equation model were used and using software SPSS 24 and AMOS 24 were used. Results: The results of the analysis showed that there is a significant positive and direct relationship between the psychological needs of employees with the experience of flow at work work and the organizational commitment of the organization (P